Reduced risk of CIN2+ recurrence in women immunized with a 9-valent HPV vaccine post-excision: Retrospective cohort study - Vladimír Dvořák; Marek Petráš; Vladimír Dvořák; Danuše Lomozová; Pavel Dlouhý; Ivana Králová Lesná; Radovan Pilka (Taylor & Francis Group, 2024)
ABSTRACTThe main aim of our study was to investigate the specific contribution of a 9-valent human papillomavirus vaccine (9vHPV) to the recurrence risk of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) in women vaccinated post-excision. Therefore, we conducted a retrospective monocentric cohort study in women aged 22-49 years undergoing conization between 2014 and 2023. The 9vHPV-vaccinated women were matched to unvaccinated women for age and follow-up duration in a 1:2 ratio to eliminate allocation bias. The risk of CIN2+ recurrence was estimated by the incidence rate ratio using Poisson regression with adjustment for comorbidities, smoking status, nulliparity, CIN grade, positive cone margin, and HPV genotypes. The CIN2+ recurrence rates in 147 women enrolled in the analysis were 18 and 2 cases per 100,000 person-days for unvaccinated and vaccinated women, respectively, during a mean follow-up period of 30 months (±22 months). A reduction in CIN2+ recurrences by 90% (95% confidence interval: 12-99%) was documented in 9vHPV-vaccinated participants compared to women undergoing only surgical excision. Moreover, vaccinated women with a positive cone margin showed a 42% (though non-significant) reduction in relapse (p = .661). Full post-conization vaccination with the 9vHPV contributed to an additional reduction in the risk of CIN2+ recurrence. This finding is consistent with current knowledge and suggests a high adjuvant effect of the 9vHPV vaccine.